Incomplete contracts and excludable public goods - Felix Bierbrauer (Max Planck Institute for Research on Collective Goods, 2010)
We study the provision of an excludable public good to discuss whether the imposition of participation constraints is desirable. It is shown that this question may equivalently be cast as follows: should a firm that produces a public good receive tax revenues, or face a self-financing requirement. The main result is that the desirability of participation constraints is shaped by an equity-efficiency tradeoff: While first-best is out of reach with participation constraints, their imposition yields a more equitable distribution of the surplus. This result relies on an incomplete contracts perspective. With a benevolent mechanism designer, participation constraints are never desirable.
Keywords: D82; D86; H41; L51; 330; Mechanism Design; Incomplete Contracts; Public Goods; Regulation